Viewing Authentic Leadership Through a Bourdieusian Lens: Understanding Gender and Leadership as Social Action. (November 2017) - Fox-Kirk, Wendy
The Problem: Many leadership development activities in modern organizations focus on the individual, either finding an individual with the secret sauce, named leadership potential, or training the individual in so-called effective leadership competencies. For women, this focus often leads to a 'fix the women' approach. Avolio and Gardner's Authentic Leadership (AL) theory with its overemphasis on the individual and narrow definitions of what it means to be 'authentic' reinforces the concept of the 'ideal leader' as the hero who will rid organizations of unethical practice. The theory's lack of attention to the role of context leads to errors in our understanding of gender and leadership, and perpetuates discrimination. The Solution: Bourdieu's Social Theory is used to explore AL theory with a view to illuminating the role of power and privilege inherent in this concept. The Stakeholders: Stakeholders are leadership development practitioners and HR specialists who are interested in reducing inequalities in organizational practices.